2014
DOI: 10.1159/000358863
|View full text |Cite
|
Sign up to set email alerts
|

The Latex Story

Abstract: The milky sap of the rubber tree Hevea brasiliensis is the source of the commercial production of natural rubber latex (NRL) devices, and also represents a source of potent allergenic proteins. NRL materials were introduced in the health care field in about 1840 with the advent of technical abilities to produce suitable and flexible NRL materials for medical products, especially gloves. In the late 1980s, with the increase of transmittable diseases, particularly HIV infection, the use of NRL gloves increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 50 publications
1
31
0
8
Order By: Relevance
“…A similar decline has been reported for HCWs . It is well known that HCWs are at higher risk of acquiring NRL allergy than the general population . Because of differences in study populations, test methods, and interventions, it is not possible to directly compare our data with results from studies focusing on HCWs.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A similar decline has been reported for HCWs . It is well known that HCWs are at higher risk of acquiring NRL allergy than the general population . Because of differences in study populations, test methods, and interventions, it is not possible to directly compare our data with results from studies focusing on HCWs.…”
Section: Discussionsupporting
confidence: 72%
“…It is well known that NRL, birch pollen, plants and some foods show cross‐reactivity . Our study showed that 64% of the NRL‐sensitized patients had a concomitant positive prick test reaction to birch pollen (Table ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Additionally, in children with spina bifida also a high prevalence of latex sensitization (up to 72%) was observed. The milky sap of the rubber tree Hevea brasiliensis is the source for the production of commercial natural rubber latex (NRL) devices and represents also a source of potent allergenic proteins (Fig. ).…”
Section: The Allergen Sourcesmentioning
confidence: 99%
“…Sensitization to latex proteins is found in health care workers, in patients with atopic diathesis, and is especially common in patients with spina bifi da or urogenital malformations [ 52,53 ] . Sensitization to latex proteins is found in health care workers, in patients with atopic diathesis, and is especially common in patients with spina bifi da or urogenital malformations [ 52,53 ] .…”
Section: Latexmentioning
confidence: 99%